Pengembangan LKPD Berbasis Multirepresentasi untuk Meningkatkan Kemampuan Problem Solving Siswa SMP pada Pembelajaran IPA - Rifta Maulani Nur Imamah; Supeno Supeno; Aris Singgih Budiarso (Departement of Mathematics Education, 2024)
This study aims to explain the validity, practicality and effectiveness of multirepresentation-based LKPD products in improving junior high school students' problem solving skills in science learning. The research method applied is Research and Development by applying the ADDIE development model which involves 5 stages. Techniques used in data collection involve observation, interviews, questionnaires, tests and documentation. Instruments to collect data include validation sheets, learning implementation observation sheets, test sheets, and questionnaire sheets. The average percentage of validity of multirepresentation-based LKPD reached 86.97%, which was categorized as valid. Meanwhile, the practicality score of multirepresentation-based LKPD has an average percentage of 86.45%, which is categorized as very practical. The effectiveness of multirepresentation-based LKPD measured through the N-gain formula is 0.53, including in the category of moderate success. In addition, student responses in the questionnaire reached an average percentage of 85.39%, which indicated that student responses were in the very good category. Based on the results of the study, it can be concluded that the development of multirepresentation-based LKPD is considered to have a fairly high level of validity, practicality and effectiveness in improving junior high school students' problem solving skills in science learning.